Evaluation of the “rotation model by seasons” as na active teaching-learning method Applied to the teaching of endodontics (Research, Society and Development, 2022)
This research aimed to evaluate the perception of students about the active model of teaching-learning ''rotation by stations'' applied to the teaching of endodontics. A survey was conducted, through a questionnaire, through the online platform "Google Forms", sent to students enrolled in the endodontics course of the School of Dentistry of Recife – FOR. The questionnaire consisted of multiple choice items and a short answer question, elaborated by the authors of the research, in order to analyze the satisfaction of students who participated in the class on diagnosis of pulp alterations. According to questionnaire responses, all students, who participated in the research, agreed that the active method rotation by stations contributed to the learning of the content "diagnosis of pulp alterations". It was found that the students were satisfied with practicing this active methodology, including, the majority said that they would like new learning stations in other curricular components. It was concluded that there was the recognition of efficacy of the station rotation model as an innovative tool in the teaching-learning process in endodontics.